2011
DOI: 10.1097/qai.0b013e31821e9bca
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized, Clinical Trial to Evaluate the Impact of Regular Physical Activity on the Quality of Life, Body Morphology and Metabolic Parameters of Patients With AIDS in Salvador, Brazil

Abstract: The practice of regular exercise, coupled with nutritional guidance, in individuals with HIV/AIDS significantly improves the quality of life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
148
0
5

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(160 citation statements)
references
References 15 publications
7
148
0
5
Order By: Relevance
“…Exercise has been shown to reduce WC in HIV-patients (35); therefore, there may be a role for exercise as a potential strategy to improve nutritional status and, consequently, QoL (31,35). In contrast to the limited available evidence on AMA and QoL suggesting a positive relationship between the two (36), an inverse relationship was found in the present study, where the lowest QoL scores were observed in subjects with ≥ adequate AMA measurements (though similar scores were observed for lower than adequate and adequate categories).…”
Section: Discussionmentioning
confidence: 99%
“…Exercise has been shown to reduce WC in HIV-patients (35); therefore, there may be a role for exercise as a potential strategy to improve nutritional status and, consequently, QoL (31,35). In contrast to the limited available evidence on AMA and QoL suggesting a positive relationship between the two (36), an inverse relationship was found in the present study, where the lowest QoL scores were observed in subjects with ≥ adequate AMA measurements (though similar scores were observed for lower than adequate and adequate categories).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it has the benefi t of being inexpensive and easy to use and is recommended by the World Health Organization 17,50 . St udies have demonstrated the benefi cial effects of regular physical activity, including improved metabolic profi le 50 , body composition, and quality of life 51,52 , in HIV-infected individuals.…”
Section: Tien and Grunfeldmentioning
confidence: 99%
“…A recently published randomized clinical trial evaluated the impact of regular physical activity on the quality of life, body morphology, and metabolic parameters in patients with AIDS, although the issue of chronic inflammation and immune activation was not investigated. 58 In this study, patients were randomly assigned to receive a 1-h supervised gym class three times a week plus monthly nutritional counseling (intervention group) or to participate in monthly workshops to discuss the importance of physical activity and receive nutritional counseling (control group). After intervention, the exercise group showed a decrease in fat mass, resting heart rate, waist circumference, and serum glucose, as well as an increase in muscle mass, CD4…”
Section: -57mentioning
confidence: 99%